Decreased Performance and Return to Play Following Anterior Cruciate Ligament Reconstruction in National Football League Wide Receivers - Colin J. Burgess, D.O; Erik Stapleton, D.O., M.S; Kenneth Choy, B.A; Cesar Iturriaga, M.D; Randy M. Cohn, M.D (Elsevier, 2021)
Purpose: To identify the time to return to play (RTP) and evaluate the performance level in wide receivers in the National Football League following anterior cruciate ligament (ACL) reconstruction. Methods: A total of 29 wide receivers in the National Football League who underwent ACL reconstruction between 2013 and 2017 who met inclusion criteria were retrospectively identified and reviewed. For each player, a matched control with similar demographics was identified to compare various in-game performance measurements and seasons played. Results: Of the wide receivers that met the inclusion criteria, 9 of 29 (31%) did not RTP in a regular season game following ACL reconstruction. For players who did RTP, 20 of 29 (69%), the average time was 10.9 months (331.4 ± 41.6 days). When we compared the tear group with the matched control cohort, players with ACL tears ended their careers on an average of 1.9 seasons earlier (2.2 vs 4.1 seasons, P < .001) and also played less than half the number of games (25.5 vs 56.6 games, P = .001), respectively. Those that RTP also saw decreased performance statistics in targets (353.6 vs 125.2 P < .001), receptions (208.0 vs 74.4, P = .001), receiving yards (2691.0 vs 987.9, P = .001), and touchdowns (17.4 vs 6.2, P = .002). Conclusions: Sixty-nine percent of wide receivers who underwent ACL reconstruction were able to RTP at an average of 10.9 months, or 331.4 days. Despite the majority of players being able to RTP, there was a significant decrease in both statistical performance and career duration. Level of Evidence: Level III, case-control study.